THE NEXUS BETWEEN FIRM SPECIFIC FACTORS, MACROECONOMIC FACTORS AND FIRM PERFORMANCE OF TEXTILE SECTOR OF BANGLADESH - Mahmud, Imran; Fahad, Hossain Ahmmed; Rahman, Atkia Nabiha (Asian Finance & Banking Review, 2021)
The purpose of this study is to identify the determinant factors of the profitability of textile sector of Bangladesh. To achieve this, a sample of 31 textile companies for the period of 2011 to 2019 is used. Two dependent variables- return on assets ROA (accounting measure) and Tobin’s Q (market measure) are tested using both fixed effect model and Panel corrected standard error (PCSE) model. As the PCSE regression robustly suited the dataset, this is used to explain the impact of both firm specific factors and macro-economic factors on the performance of textile firms listed in Dhaka Stock Exchange. The determinants of profitability differ depending on which measures of profitability we have taken as proxy. When ROA is taken, age, debt to equity, debt to asset, growth, asset turnover, cost effectiveness (EATC) and export growth are found significant. Among them, debt to equity, asset turnover, cost effectiveness and export growth conforms to the expected positive sign. In terms of Tobin’s Q, age, size, debt to equity, growth, cost effectiveness (EATC), board size and export growth are found having significant impact on firm performance where age, EATC, board size, and export growth conforms to the expected positive sign. JEL Classification Codes: C83, C87, L25.